O peso do recorde : como a meta do acidente zero pode dificultar a prevenção - Anna Carolinna Eduardo Pereira (2023)
With the purpose of encouraging everyone’s collaboration in the prevention of accidents at work, plaques such as “We have been without accidents for XXX days”, “Our record is YYY days” are stamped in almost all companies along with practices that aim to achieve the “zero accident” or that promote safety performance rankings between production units, teams or even individuals. Often even trophies, token awards and financial rewards are offered to commemorate safety results. Based on this context, the objective of this work was to investigate how the workers of a thermal plant that reached the result of almost 7 years without accidents with lost time related to this result reached and considered by all as a record. For that, qualitative research was carried out using the Ergonomic Work Analysis (AET) for data collection and the Grounded Theory for data analysis. Field observations, analysis of documentary records and minutes of meetings, and interviews were carried out during the workday of the plant’s workers over a period of 1 year and 8 months. As, throughout the data collection, significant questions for the research emerged from the interviews, observations or documents, interviews of selfconfrontation of information were carried out to understand the workers’ decisions. Thus, this work aimed to demonstrate how the record, behind a logic of overvaluation of the result, influenced the behavior of workers and the weakening of security. As a result, four cases of accidents emerged that occurred within this period of commemoration of the safety record and that generated controversy and discomfort among workers because of the status achieved by the plant. An attempt was also made to show ways to strengthen safety at the plant.